(untitled) (Publicacions de la Universitat de València, 2024)
This volume traces Th. More’s intellectual and political connections with Spain through eight scholarly contributions. Olivares examines Erasmus’s role in linking Arias Montano to More’s legacy amid Counter-Reformation censorship. Cabrillana decodes More’s Lucian translations to reveal his moral-aesthetic priorities, while Phelippeau juxtaposes ‘Utopia’ with Venetian governance models resisting Habsburg hegemony. Ureña explores digital humanities’ challenges in Morean studies, and Lillo reconstructs Spanish accounts of More’s trial through several manuscripts. Fuentes analyzes Mary Tudor’s Erasmian translations, and Zunino maps Sevillian networks that cultivated More’s posthumous reputation via Herrera’s 1592 biography. The volume concludes with the editor’s exploration of More and Vives’ nuanced just-war theories, challenging some naive pacifist interpretations by contextualizing their pragmatic responses to Ottoman expansion. Bridging literary analysis, archival research, and transnational historiography, these essays illuminate Spain’s enduring role in shaping More’s critique of power and his Renaissance afterlife.